MEMBANGUN SISTEM KOMUNIKASI INDONESIA YANG KOLEKTIF LEWAT MEDIA TRADISIONAL - Mutiah, Mutiah (The Journal of Society and Media, 2017)
Every era has a style of leadership homeland of its own communication system, the freshest in the memory is the one-way communication system that uses the Suharto regime, the communication patterns of society become more closed and limited to this one picture of the communication system in the country. Currently, the development of communication Indonesia enlivened by the growing influence of digital media are in fact deliver Indonesian communications systems become more open, a lot of positive things that can pergola but not less any negative impact on the behavior patterns of public communication in the country. One negative impact is raised hyper personality behavior, expressions of hatred which mushroomed, spreading freedom hoax news and social conflicts that originated from the issues that were distributed via digital media. This article will reveal the traditional media in the country which is a collectivist society Indonesian media. Indonesia is a country characterized by mutual cooperation and collective and this characteristic has not completely faded, there are many people which maintains the traditional media as a collective channel for the common good, gave a small portion of the new media included in their environment. This article will present an overview of traditional media in some areas in East Java with descriptive writing method, trying to describe the data on observations and interviews later authors explain by juxtaposing concept Communication Systems Indonesia. It could be 76 | The Journal of Society & Medi a 1 ( 2 ) concluded that the traditional media is still very effectively used to establish communication patterns collectivist, together and work together in accordance with the character of Indonesian society. Certainly, from this article, the authors advise the government should appreciate each community that preserves the traditional media as the media collectivist indigenous peoples.